1999
DOI: 10.1023/a:1022606206076
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Young children with sleep problems received either "standard" or graduated ignoring treatment. Both brief treatments were superior to a wait-list control condition and resulted in comparable improvements in bedtime and nighttime sleep problems. At bedtime, the treatments did not differ with respect to maternal compliance and stress. For nighttime wakings, mothers in the graduated ignoring group reported higher rates of compliance and less treatment-related stress. Maternal characteristics predicted treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…The apparent efficacy of stimulus control techniques is beneficial as it minimises the need to utilise extinction based protocols which often have multiple side-effects (Jin et al 2013 ). Reid et al ( 1999 ) noted a drop-out rate of 20% of parent participants from extinction based interventions due to a reluctance to ignoring crying. Stimulus control interventions in comparison do not result in prolonged periods of crying or increased rates of challenging behaviours (Burke et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent efficacy of stimulus control techniques is beneficial as it minimises the need to utilise extinction based protocols which often have multiple side-effects (Jin et al 2013 ). Reid et al ( 1999 ) noted a drop-out rate of 20% of parent participants from extinction based interventions due to a reluctance to ignoring crying. Stimulus control interventions in comparison do not result in prolonged periods of crying or increased rates of challenging behaviours (Burke et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…This ADHD cluster discriminates between referred and non-referred children in clinical research. Other subscales have been used in studies of sleep behavior [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the current sample, receiving a diagnosis in the relational disorders or psychosocial problems category was not associated with parental reports of sleep difficulties. Other studies have shown an association between sleep quality and parent-child relationships [36,37], and a recent review paper highlighted the impact of behavioral sleep interventions for bedtime problems and night awakenings on secondary outcome variables such as parent-child relationships [13]. Differences in the population and type of measure (sleep and relational variables) could potentially explain the presence or absence of associations between relational disorders and sleep problems.…”
Section: Discussionmentioning
confidence: 99%